2002
DOI: 10.1097/00001610-200203000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Operative Trauma to Anal Sphincters

Abstract: Sphincter trauma after anorectal surgery is usually asymptomatic. Frequency of trauma cannot be established with the clinical examination only. The frequency of operative sphincter defects and their correlation with disorders of continence was evaluated with the endoanal ultrasound. This study includes 123 subjects who had undergone anorectal surgery in the past and were examined with endoanal ultrasound for various indications such as continence disorders, recurrent fistula, idiopathic perineal pain, or simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Because of the high rate of continence disorders after fistulotomy, 22,28,29 methods of sphincter integrity preservation, such as fibrin glue and anal fistula plugs, should be considered in female patients presenting with anterior transsphincteric fistula with Ͼ50.0% EAS involvement. Three-dimensional anorectal ultrasonography was shown to be useful in the preoperative assessment of anterior transsphincteric fistulas by quantifying the length of muscle to be transected, thereby contributing to the choice of a safe treatment approach and to the reduction of the rate of postoperative continence disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the high rate of continence disorders after fistulotomy, 22,28,29 methods of sphincter integrity preservation, such as fibrin glue and anal fistula plugs, should be considered in female patients presenting with anterior transsphincteric fistula with Ͼ50.0% EAS involvement. Three-dimensional anorectal ultrasonography was shown to be useful in the preoperative assessment of anterior transsphincteric fistulas by quantifying the length of muscle to be transected, thereby contributing to the choice of a safe treatment approach and to the reduction of the rate of postoperative continence disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Causes include changes in mucosal sensitivity and anal sphincter pressures following surgery, changes in the symmetry and closure of the anal canal following removal of haemorrhoidal tissue, and occult damage to the sphincter complex during haemorrhoidectomy. One study identified that internal sphincter damage was detectable endosonographically in over 5% of patients following open haemorrhoidectomy [67].…”
Section: Complications Of Haemorrhoidectomymentioning
confidence: 99%
“…15 Studies suggest that stretch injury from anal retractor use during surgery decreases anal resting pressures. 16,17 IAS and EAS may also be injured after anorectal surgery, although only roughly one-third of these patients reported FI 18 ; neurogenic damage and rectal ischemia may occur. 19…”
Section: Anorectal Surgerymentioning
confidence: 99%